Urban and Rural Land Management Techniques, Incorporating Appropriate Laws Affecting Land Use Resources in Nigeria - Alao, D. O.; Oladejo, E. I.; Oyakhire, M. M.; Enadeghe, G. O. (International Journal of Real Estate, 2025)
Land resource is an integral part of the Nigerian economy. The need for the utilization and management of land resources cannot be overstressed. Effective and sustainable urban and rural land management techniques, laws and policies are pointers to attaining optimality of land resource utilization and management. There is therefore, need for appropriate techniques to be employed in the use and management of land resources. The present study is a literature review and, therefore, essentially relies on published data sourced from academic journals, conference papers, thesis, and other secondary sources. This paper reviews the techniques of utilizing and managing land resources in Nigeria, vis-à-vis the extent of effectiveness and sustainability. If further considers the laws affecting land use and resources in Nigeria. The techniques of land utilization and management encompass the traditional, critical chain project management, process-based management and result based management approaches. All the approaches require transparency and a mindset that focuses on now and future. For adequate utilization and management of land resources, policymakers, researchers and stakeholders should employ transparent tools as well as the relevant laws that will not only think of now but also future benefits in Nigeria. The Land Use Act and other related laws are overdue for review.
Keywords: Techniques; land resources; urban; rural; utilization; management and Nigeria